(untitled) (International Integralize Scientific, 2026)
Waterborne diseases remain a significant public health issue in Brazil, being directly associated with sanitation conditions and socio-environmental determinants. This study aimed to analyze the epidemiological trends of these diseases in Brazil from 2010 to 2024, as well as their association with socio-environmental factors. This is a quantitative, descriptive, and analytical study with an ecological design and time-series approach, based on secondary data obtained from official health and statistical information systems. The results showed an overall decreasing trend in disease incidence over the analyzed period, although with occasional fluctuations and persistent regional inequalities, with higher rates in the North and Northeast regions. Statistical analysis revealed significant associations between disease incidence and variables such as access to treated water, sewage coverage, and income, highlighting the influence of socio-environmental determinants. It is concluded that, despite improvements, waterborne diseases still represent a relevant challenge, reinforcing the need to expand public policies focused on sanitation and social inequality reduction.